Shell Thickness of Turkey Eggs Affects Cardiac Physiology and Embryo Survival - Christensen, V.L.; Bagley, L.G.; Olson, T.; Grimes, J.L.; Rowland, R.D.; Ort, D.T. (International Journal of Poultry Science, 2006)
Supplementing 500 ppm of a chelated calcium proteinate (CCP) to a commercial breeder diet resulted in thicker shells and improved embryo livability. The CCP diet was fed to one half of a flock of breeders on a commercial farm that was suffering shell problems, and a standard commercial diet was fed to the remaining half. Egg production, eggshell thickness, fertility and hatchability of eggs were all monitored over an 18 wk laying period. Feeding CCP increased shell thickness and reduced numbers of cull eggs after 8 wk of lay compared to the controls. When differences in eggshell thickness were seen after 10 weeks of egg production, embryo survival and cardiac physiology were examined in three trials comparing the thicker shells to thin. Thick shells (0.44 versus 0.39 mm) improved embryo survival 2% by decreasing numbers of embryos dying late in development compared to controls and affected cardiac physiology. Thus, thick shells may improve embryo viability by affecting cardiac health during the plateau stage in oxygen consumption.